Improving service performance in banking using quality adjusted data envelopment analysis - Juraj Kopecsni (Charles University in Prague, Institute of Economic Studies (IES), 2010)
The goal of this research is to describe the application of data envelopment analysis (DEA) to the performance evaluations of bank branches. Special attention is focused on how to incorporate the quality dimension into branch efficiency. DEA will apply to a set of micro-data from a Czech commercial bank branch network. In the banking sector, providing services quality is one of the key focuses. Therefore, the quality dimension should be incorporated into the DEA model. The goal of the quality adjusted DEA model is to identify best practice branches that work efficiently and at the same time provide services with high quality. This model avoids productivity-quality tradeoff, which is present by the standard DEA model. The quality of services is measured by customer service, mystery shopping and calls, client information index, retention, and client product penetration. Main determinants of efficiency and quality level are branch size and region via purchasing power.
Keywords: C14; C44; C61; L8; 330; quality adjusted DEA; branch performance; scale efficiency; return to scale; Bank; Performance-Messung; Dienstleistungsqualität; Data-Envelopment-Analyse; Tschechische Republik